Rational versus emotional appeals for smartphone advertisement in triggering UTAR undergraduates purchase intention - Yeo, Wan Teng; Ling, Hui Yin; Chai, Ming Mei (2020)
In an era where technology advanced at unprecedented rates, people prefer to use new media for information searching as compared to legacy media. Especially for young adults, they will use their smartphone for accessing commercials, make purchases, conduct research, and operate online businesses. They like short and interesting content through new media compared to traditional broadcasting. Thus, in developing commercials, advertisers should consider the length of commercials and the media content to deliver messages to young adults effectively. When people access smartphone commercials, the most common type of broadcasting appeal that would be utilized is a rational and emotional appeal. Besides, marketers also advertised their merchandise through social platforms like YouTube, Facebook, Instagram, and etc. This study's purpose is to find out which broadcasting appeal for smartphone commercials, among logical appeal and sentimental appeal, would prompt young adult’s acquisition resolution. The analysis is performed using a qualitative methodology approach. 22 interviewees between the ages of 18 to 26 years old are involved in the interview session. Outcomes of this work would give a boost to many parties, including an advertiser, and academics.